2015
DOI: 10.1016/j.pmedr.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of a randomised controlled trial comparing fall prevention using exercise with or without the support of motivational interviewing

Abstract: ObjectiveThe aim of this investigation was to study the feasibility of a randomised controlled trial (RCT) based on a multicentre fall prevention intervention including exercise with or without motivational interviewing compared to standard care in community-living people 75 years and older.MethodThe feasibility of a three-armed, randomised controlled trial was evaluated according to the following: process, resources, management by questionnaire, and treatment outcomes. The outcome measures were fall frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Our findings clearly demonstrated that PTs considered the OEP to be an easy and applicable evidencebased program in clinical practice, even if some smaller challenges were found. These findings are in line with results presented in a previous study that evaluated the feasibility of the OEP from the PTs' point of view in a Swedish primary care setting, as it confirmed that the OEP is a feasible intervention within the target context (Arkkukangas et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings clearly demonstrated that PTs considered the OEP to be an easy and applicable evidencebased program in clinical practice, even if some smaller challenges were found. These findings are in line with results presented in a previous study that evaluated the feasibility of the OEP from the PTs' point of view in a Swedish primary care setting, as it confirmed that the OEP is a feasible intervention within the target context (Arkkukangas et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The search returned 4006 records, of which 108 trials involving 23 407 participants were eligible for inclusion (figure 1). 18 The characteristics of the 108 included trials are summarised in online supplementary material B 10 19–125…”
Section: Resultsmentioning
confidence: 99%
“…At 6-months' reassessment, Yang et al (2012) had similar results of compliance. Additionally, motivational factors also influence compliance to exercise ( Arkkukangas et al, 2015 ; McMahon et al, 2016 ; Sherrington et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%